Identifying interactive biological pathways associated with reading disability. Issue 8 (28th June 2020) - Lancaster, Hope Sparks; Liu, Xiaonan; Dinu, Valentin; Li, Jing
Abstract: Introduction: Past research has suggested that reading disability is a complex disorder involving genetic and environment contributions, as well as gene–gene and gene–environment interaction, but to date little is known about the underlying mechanisms. Method: Using the Avon Longitudinal Study of Parents and Children, we assessed the contributions of genetic, demographic, and environmental variables on case–control status using machine learning. We investigated the functional interactions between genes using pathway and network analysis. Results: Our results support a systems approach to studying the etiology of reading disability with many genes (e.g., RAPGEF2, KIAA0319, DLC1 ) and biological pathways (e.g., neuron migration, positive regulation of dendrite regulation, nervous system development) interacting with each other. We found that single nucleotide variants within genes often had opposite effects and that enriched biological pathways were mediated by neuron migration. We also identified behavioral (i.e., receptive language, nonverbal intelligence, and vocabulary), demographic (i.e., mother's highest education), and environmental (i.e., birthweight) factors that influenced case–control status when accounting for genetic information. Discussion: The behavioral and demographic factors were suggested to be protective against reading disability status, while birthweight conveyed risk. We provided supporting evidence that reading disability has a complex biological and environmental etiology and that there may be a shared genetic and neurobiological architecture for reading (dis)ability. Abstract : We completed a pilot analysis using elastic net regression and pathway analysis. Our pilot results highlight the role of brain development and neuron organization biological pathways in reading disability status.